Evaporated SexTe1‐x Thin Films with Tunable Bandgaps for Short‐Wave Infrared Photodetectors. Issue 38 (9th August 2020) - Tan, Chaoliang; Amani, Matin; Zhao, Chunsong; Hettick, Mark; Song, Xiaohui; Lien, Der‐Hsien; Li, Hao; Yeh, Matthew; Shrestha, Vivek Raj; Crozier, Kenneth B.; Scott, Mary C.; Javey, Ali
Abstract: Semiconducting absorbers in high‐performance short‐wave infrared (SWIR) photodetectors and imaging sensor arrays are dominated by single‐crystalline germanium and III–V semiconductors. However, these materials require complex growth and device fabrication procedures. Here, thermally evaporated Se x Te1‐ x alloy thin films with tunable bandgaps for the fabrication of high‐performance SWIR photodetectors are reported. From absorption measurements, it is shown that the bandgaps of Se x Te1‐ x films can be tuned continuously from 0.31 eV (Te) to 1.87 eV (Se). Owing to their tunable bandgaps, the peak responsivity position and photoresponse edge of Se x Te1‐ x film‐based photoconductors can be tuned in the SWIR regime. By using an optical cavity substrate consisting of Au/Al2 O3 to enhance its absorption near the bandgap edge, the Se0.32 Te0.68 film (an optical bandgap of ≈0.8 eV)‐based photoconductor exhibits a cut‐off wavelength at ≈1.7 μm and gives a responsivity of 1.5 AW −1 and implied detectivity of 6.5 × 10 10 cm Hz 1/2 W −1 at 1.55 μm at room temperature. Importantly, the nature of the thermal evaporation process enables the fabrication of Se0.32 Te0.68 ‐based 42 × 42 focal plane arrays with good pixel uniformity, demonstrating the potential of this unique material system used for infrared imaging sensor systems. Abstract : Thermally evaporated Se x Te1‐ x alloy thin films with tunable bandgaps (from 0.31 eV to 1.87 eV) are prepared for the fabrication of high‐performance short‐wave infrared photodetectors. The Se0.32 Te0.68 ‐film‐based photoconductor fabricated on an optical cavity substrate exhibits a cut‐off wavelength at ≈1.7 μm and gives a responsivity of 1.5 AW −1 and implied detectivity of 6.5 × 10 10 cm Hz 1/2 W −1 at 1.55 μm at room temperature.